Pengembangan media pembelajaran aplikasi ECCJ (Education Cultural Central Java) pada materi keragaman budaya Geografi - Muhammad Afkaar Aafaani; Fatiya Rosyida; Djoko Soelistijo; Purwanto Purwanto (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
The renewal of learning media in the world of education functions to make it easier for teachers to convey messages or information to students. To convey messages in the application of the 2013 curriculum learning, it is expected that teachers need to use technology and information to fulfill educational attainment in the cognitive, affective, and psychomotor domains. Utilization of learning media at SMAN 1 Pangkah that teachers in the learning process still have limitations in using media, so that students become less enthusiastic and reduce learning motivation. The purpose of this development study is to use flash player software on cultural diversity materials to create applications in the form of animation, text, images, video, and audio. The research design used Sugiyono's methodology which was modified into seven stages. The results of the validation by the media and materials show that they have met the eligibility criteria. The results of the due diligence at SMAN 1 Pangkah in the small group test averaged 82 percent with a teacher response of 89 percent and in the large group test with an average of 90 percent with a teacher response of 96 percent. Based on the results of the eligibility criteria for the responses of media experts, materials, teachers, and students stated that learning application media developed on cultural diversity material could increase student activity and interest in the learning process. The developed learning application media still has deficiencies in aspects of evaluation appearance and graphic design that are not yet 3D. It is hoped that future researchers can improve and maximize the appearance of evaluation and graphic design. Pembaharuan media pembelajaran dalam dunia pendidikan berfungsi untuk mempermudah guru dalam menyampaikan pesan atau informasi kepada peserta didik. Untuk menyampaikan pesan dalam penerapan pembelajaran kurikulum 2013 diharapkan bahwa guru perlu menggunakan teknologi dan informasi untuk memenuhi tercapainya pendidikan dalam ranah kognitif, afektif, dan psikomotor. Pemanfaatan media pembelajaran di SMAN 1 Pangkah bahwa guru dalam proses pembelajaran masih terdapat keterbatasan penggunaan media, sehingga peserta didik menjadi kurang semangat dan menurunkan motivasi belajar. Tujuan dari kajian pengembangan ini adalah menggunakan software flash player pada materi keragaman budaya untuk membuat aplikasi berupa animasi, teks, gambar, video, dan audio. Desain penelitian menggunakan metodologi dari sugiyono yang dimodifikasi menjadi tujuh tahapan. Hasil validasi oleh media dan materi menunjukan telah memenuhi kriteria kelayakan. Hasil uji kelayakan di SMAN 1 Pangkah pada uji kelompok kecil rata-rata 82 persen dengan tanggapan guru 89 persen dan uji kelompok besar dengan rata-rata 90 persen dengan tanggapan guru 96 persen. Berdasarkan hasil kriteria kelayakan tanggapan ahli media, materi, guru, dan peserta didik menyatakan media aplikasi pembelajaran yang dikembangan pada materi keragaman budaya dapat meningkatkan keaktifan dan ketertarikan sisiwa terhadap proses pembelajaran. Media aplikasi pembelajaran yang dikembangkan masih mempunyai kekurangan pada aspek tampilan evaluasi dan desain grafis yang belum 3D. Diharapkan bagi peneliti selanjutnya bisa memperbaiki dan memaksimalkan pada tampilan evaluasi dan desain grafis.